FACTORS AFFECTING FIRM VALUE IN INDONESIA’S PROPERTY AND REAL ESTATE FIRMS - Lawinata, Karen; Susanto, Liana (Graduate Program of Universitas Tarumanagara, 2023)
This research was conducted to obtain empirical evidence regarding the influence of profitability, liquidity and leverage as independent variables on the dependent variable, namely firm value in the property and real estate sector listed on the Indonesia Stock Exchange (BEI) with the research year being 2019 to 2021. Parameters used to measure firm value is the book value (PBV) which is calculated by dividing the current share price by the book value per share. Profitability in this research is proxied by Return on Assets (ROA) which is calculated by dividing net profit by total assets. Liquidity in this research is proxied by the Current Ration (CR) which is calculated by dividing current assets by current liabilities. Leverage in this research is proxied by the Debt-to-Equity Ratio (DER) which is calculated by dividing total debt by total equity. The number of samples in this research was 34 property and real estate companies listed on the Indonesia Stock Exchange in 2019 - 2021. The sampling technique used in this research was the purposive sampling method and the analysis technique used to test the hypothesis in this research was using multiple linear regression analysis technique. The statistical tool used to test the sample in this study used SPSS 26. The results of data processing in this study show that profitability has a significant positive influence on firm value, while liquidity and leverage do not have a significant influence on firm value.